2020
DOI: 10.3389/fpls.2020.537766
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Analysis for Phosphorus Use Efficiency Traits in Mungbean (Vigna radiata L. Wilczek) Using Genotyping by Sequencing Approach

Abstract: Mungbean (Vigna radiata L. Wilczek) is an annual grain legume crop affected by low availability of phosphorus. Phosphorus deficiency mainly affects the growth and development of plants along with changes in root morphology and increase in rootto-shoot ratio. Deciphering the genetic basis of phosphorus use efficiency (PUE) traits can benefit our understanding of mungbean tolerance to low-phosphorus condition. To address this issue, 144 diverse mungbean genotypes were evaluated for 12 PUE traits under hydroponic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 117 publications
4
39
0
Order By: Relevance
“…Further, this SNP locus was associated with total shoot P content and shoot DW in different models (Supplementary Table 1 and Figure 2). Such shared associations were also reported using different models in mungbean PUE (Reddy et al, 2020). A recent study reported that low expression of selected fasciclin-like arabinogalactan protein genes led to kernel abortion in maize (Zea mays) and Arabidopsis thaliana seeds (Cagnola et al, 2018).…”
Section: Discussionsupporting
confidence: 60%
“…Further, this SNP locus was associated with total shoot P content and shoot DW in different models (Supplementary Table 1 and Figure 2). Such shared associations were also reported using different models in mungbean PUE (Reddy et al, 2020). A recent study reported that low expression of selected fasciclin-like arabinogalactan protein genes led to kernel abortion in maize (Zea mays) and Arabidopsis thaliana seeds (Cagnola et al, 2018).…”
Section: Discussionsupporting
confidence: 60%
“…Lentil genotypes differed for their reaction to the P de cit mediums. Various crops showed variation for their reaction to P, wheat [47][48], oats, barley, triticale and rye [49], maize [50], cotton [51][52], groundnut [53], brassica [54], soybean [55], faba bean [56], common bean [57], lentil [58], and the mungbean [59]. Many studies routinely used targeting to few measures of P-use e ciency [60] and other studies targeted speci c root architectural traits [61] and while another vital trait root hair formation was also considered [62].…”
Section: Discussionmentioning
confidence: 99%
“…Tissue P concentration, biomass accumulation, and P uptake were the most sensitive P-de ciency traits to stress, as reported in mungbean (Pandey et al, 2014) and soybean . Wide genotypic variation in phosphorus use e ciency (PUE) has been reported in mungbean (Pandey et al 2013;Meena et al 2020;Reddy et al 2020), indicating that Pe cient genotypes uptake more P to shoots than roots. This suggests that P translocation from roots to shoots is an adaptive strategy to increase PUE (Krishnappa et al 2011;Krishnappa and Hussain 2014).…”
Section: Discussionmentioning
confidence: 99%